Pengaruh Kinerja Dan Efektivitas Kerja Aparat Pemerintah Terhadap Kepuasan MasyarakatDi Kelurahan Tualang KecamatanPerbaunganKabupatenSerdang Bedagai - Monica, Silvia; Samosir, Suhaila Husna (LPPM Universitas Labuhanbatu, 2021)
This study aims to determine the effect of performance and work effectiveness of government officials on community satisfaction in Tualang Village, Perbaungan District, Serdang Bedagai Regency. This study uses a quantitative descriptive approach with multiple regression analysis technique, which aims to determine the relationship between two or more variables. The population of this research is the Tualang Village community, which is 2,340 heads of families. This study took a sample using the Slovin formula and obtained a sample of 96 people. The suitability test using t test and f test was carried out to test the partial and simultaneous effect between the independent variable and the dependent variable with the assumption that other variables are considered constant. The results of this study are; first, the t-value of X1 is 7.931 with a sig level of 0.000 greater than the t-table 1.986. The t-count has a positive value indicating that X1 has a unidirectional relationship with Y. So it can be concluded that the Performance variable has a positive and significant effect on Community Satisfaction. Second, the t value of X2 is 3.727 with a sig level of 0.000 which is greater than the t table of 1.986. t count is positive indicating that X2 has a direct relationship with Y. So it can be concluded that the Work Effectiveness variable has a positive and significant effect on Community Satisfaction. Third, the calculated f value is 122,386 with a sig level of 0.000 which is greater than f table 3.09. f count is positive indicating that X1 and X2 simultaneously have a relationship in the direction of Y, so it can be concluded that the variables of Performance and Work Effectiveness simultaneously have a positive and significant effect on Community Satisfaction. The value of R square is 0.725. This means that the effect of variable X on variable Y is 72.5%, while the remaining 0.275 or 27.5% is influenced by other factors such as work discipline, atmosphere and conditions of the work environment.